DAYA TARIK DESTINASI PARIWISATA BUDAYA STUDI KASUS MUSEUM BAHARI JAKARTA - Priyanto Priyanto (Universitas Pakuan, 2021)
Abstract This study aims to examine the use of the Jakarta Maritime Museum's resources as an attraction for cultural tourism destinations. This study uses a qualitative research approach with descriptive analysis. The stages in this research are observation, description and interpretation through the approach of the concept of cultural tourism and the concept of museology. Through this research, it is hoped that optimal results will be obtained on how to use Jakarta's maritime museum resources as an attraction for cultural tourism destinations. The results of this research are also expected to be able to present the role and function of the Jakarta Maritime Museum through its various presentations that can be useful for the community. Keywords: Cultural Tourism, Jakarta Maritime Museum AbstrakPenelitian ini bertujuan untuk mengkaji Pemanfaatan Sumber Daya Museum Bahari Jakarta Sebagai Daya Tarik Destinasi Wisata Budaya. Penelitian ini menggunakan metode pendekatan penelitian kualitatif dengan analisis deskriptif. Tahapan dalam penelitian ini adalah observasi, deskripsi dan interpretasi melalui pendekatan konsep pariwisata budaya dan konsep museologi. Melalui penelitian ini diharapkan akan memperoleh hasil yang optimal bagaimana pemanfaatan sumber daya museum bahari Jakarta sebagai daya tarik destinasi wisata budaya. Hasil penelitian ini juga diharapkan akan dapat menyajikan peran dan fungsi Museum Bahari Jakarta melalui berbagai penyajiannya dapat bermanfaat untuk masyarakat. Kata Kunci : Pariwisata Budaya, Museum Bahari Jakarta